Optimizing MATLAB Applications to Advance Automotive System Development - Ibrahim, Fauzi; Hadi, Agung Efriyo; Marjuni, Teuku; Apriyanto, Agus; Putri, Novia Utami; Wahyudi, Retno; Sembiring, Alexander; Murti, Adam Wisnu (Jurnal Rekayasa Teknologi dan sains, 2025)
The automotive industry continues to evolve with the integration of sophisticated computational tools to optimize design, analysis, and control systems. MATLAB, known for its powerful numerical and simulation capabilities, has emerged as a key tool in achieving efficiency, accuracy, and automation across automotive engineering processes. This study explores the strategic utilization of MATLAB in areas such as engine modeling, vehicle dynamics simulation, embedded system development, and control system design. The research employs a qualitative method supported by case studies from various industrial applications, highlighting how MATLAB toolboxes like Simulink, Stateflow, and Simscape contribute to reducing development time and improving system performance. Results show that optimized MATLAB use not only accelerates prototyping and testing phases but also enhances precision in control strategies, especially for electric and autonomous vehicles. This paper concludes by emphasizing the growing importance of MATLAB proficiency among automotive engineers and its role in driving digital transformation in the industry.